(untitled) (Research, Society and Development, 2026)
The occipital venous sinus is the smallest venous sinus described and typically communicates cranially with the confluence of sinuses and caudally with the vertebral venous plexus, resulting in the formation of a single groove between the internal occipital crest and the jugular foramen. Additionally, the sigmoid sinuses are responsible for draining the transverse sinuses on each side toward the internal jugular vein, which defines a bilaterally present groove on the petrous surface of the temporal bone. The aim of this case report was to describe an uncommon anatomical variation related to these grooves, identified in an adult dry skull from the Human Anatomy Laboratory of an educational institution located in the interior of the state of São Paulo, Brazil. Furthermore, to complement the study, a literature review was conducted in the PubMed and SciELO databases using the descriptors “occipital venous sinus” and “anatomic variation,” combined with the Boolean operator AND. Examination of the specimen revealed a peculiar anatomical variation: the groove of the occipital venous sinus was oblique and bilateral, with both depressions originating from the internal occipital crest and extending toward the groove of the ipsilateral sigmoid sinus. In addition, the groove of the right sigmoid sinus was nearly imperceptible, suggesting the presence of asymmetry in the cranial structure. Thus, understanding such variations is essential for planning neurosurgical interventions, in order to avoid complications and improve patient care.